Progress with rotavirus vaccines: summary of the Tenth International Rotavirus Symposium. (February 2013) - Parashar, Umesh; Steele, Duncan; Neuzil, Kathleen; Quadros, Ciro de; Tharmaphornpilas, Piyanit; Serhan, Fatima; Santosham, Mathu; Patel, Manish; Glass, Roger
Tenth International Rotavirus Symposium Bangkok, Thailand, 19–21 September 2012 Over 350 scientific, public and private sector experts from 47 countries convened at the Tenth International Rotavirus Symposium in Bangkok, Thailand on 19–21 September 2012 to discuss progress in the prevention and control of rotavirus, the leading cause of diarrhea hospitalizations and deaths among young children worldwide. Participants discussed data on the burden and epidemiology of rotavirus disease, results of trials of rotavirus vaccines, postmarketing data on vaccine impact and safety from countries that have implemented rotavirus vaccination programs, new insights in rotavirus pathogenesis, immunity and strain diversity, and key issues related to vaccine policy and introduction.